Global Distribution of Non‐algal Particles From Ocean Color Data and Implications for Phytoplankton Biomass Detection. Issue 15 (11th August 2018) - Bellacicco, M.; Volpe, G.; Briggs, N.; Brando, V.; Pitarch, J.; Landolfi, A.; Colella, S.; Marullo, S.; Santoleri, R.
Abstract: In the last few decades, phytoplankton biomass has been commonly studied from space. However, satellite analysis of non‐algal particles (NAPs), including heterotrophic bacteria and viruses, is relatively recent. In this work, we estimate the backscattering coefficient associated with the NAP fraction that does not covary with chlorophyll based on satellite particulate backscattering coefficient and chlorophyll (bbp NAP). bbp NAP is computed at 100‐km resolution using 19 years of monthly satellite data. We find clear differences in b bp NAP between northern and southern oceans. High bbp NAP values are found in the Arctic and Southern Oceans, the North Atlantic area influenced by the Gulf Stream current, as well as shelf regions (i.e., Patagonian shelf) affected by upwelling regimes. Low correlation between chlorophyll and backscattering prevents precise bbp NAP estimations in oligotrophic areas (e.g., subtropical gyres). These bbp NAP estimations lead to a reduction to half in satellite‐based phytoplankton biomass estimates respect to previously published results. Plain Language Summary: In the ocean, there are different seawater constituents that contribute to the inherent optical properties: Phytoplankton is a major constituent and one of the most studied in the last decade. Other important constituents are the colored dissolved organic matter and non‐algal particles (NAPs). NAP includes (i) heterotrophic organisms such as bacteria, micrograzers, and viruses; (ii) detrital organic particles such as fecal pellets and cell debris; and (iii) mineral particles of both biogenic (e.g., calcite liths and shells) and terrestrial origin (e.g., clays and sand). This study is the first attempt to define the NAP from space, and its spatial variability, and how it contributes to refine the phytoplankton carbon biomass estimation. We estimate the backscattering coefficient associated with the NAP fraction that does not covary with chlorophyll from the satellite particulate backscattering coefficient and chlorophyll (bbpNAP). Our main results evidence a geographical variability of bbpNAP from northern to southern oceans with two distinct regimes: one associated with the productive areas in which bbpNAP and biomass are anticorrelated and another in which bbpNAP high values are in regions dominated by inorganic origin. We demonstrate that the spatial variability of bbpNAP should not be ignored. Key Points: A new pixel‐scale method is developed to compute backscattering of non‐algal particles from ocean color data The backscattering of non‐algal particles has geographical variability from northern to southern hemispheres The backscattering of non‐algal particle variability has to be taken into account in phytoplankton biomass models